STUDENTS' DIGITAL READING COMPREHENSION CHALLENGES ON ACADEMIC TEXT - Suska Rika Mukti Rahayu (JELT (Jambi-English Language Teaching), 2024)
This research aims to explore the challenges of digital reading comprehension on academic text faced by third-semester students at Jambi University. In conducting this research, the researcher used descriptive qualitative methods. Five participants participated in this research and met the criteria desired by the researcher, such as active third-semester students, students who had completed reading for academic purposes courses, and students who were willing to be involved in this research. The researcher used semi-structured interviews as an instrument in data collection. The data is then processed through three stages, namely, data reduction, data display, and drawing conclusions or verification. The final results reveal that there are two categories in the challenges of digital reading comprehension on academic text. The first category is technology issues which include low reading interest, eye strain, internet connection, concentration, and too much information. Meanwhile, the second category is academic reading comprehension challenges which include vocabulary, complex sentences, and unfamiliar topics. In conclusion, students face challenges in digital reading comprehension on academic texts, especially in aspects technology and comprehension.